Ground Zero? Let’s get real on regeneration! Report 1: State of the art and indicator selection - Giller, Kenneth E.; Pulleman, Mirjam Margreet; Sassen, Marieke; Pronk, Annette; Pratihast, Arun; Velthof, Gerard; Rahn, Eric; Barthel, Matti; Lourenço, Késia S.; Díaz, Andrea (Wageningen University & Research, 2023)
The urgency with which the world needs to combat climate change has led to ambitious commitments by leading food companies such as Nestlé. Given that a large proportion of emissions in supply chains occur during the production of commodities, focus has converged on Regenerative Agriculture as a key strategy to achieve those goals. The Regenerative Agriculture agenda coalesces around three main goals: • Reduce the Carbon Footprint • Enhance Soil Health • Enhance and safeguard Biodiversity alongside commitments to enhance smallholder producers’ incomes, to avoid child labour and to ensure a sustainable supply. The Ground Zero project aims to provide a framework of robust, easily measurable and verifiable indicators and methods for the assessment of the carbon footprint, soil health and biodiversity in cocoa and coffee production systems. The project is organised around four work packages (WPs): WP1 – Coordination; WP2 – Carbon Footprints; WP3 – Soil Health; WP4 – Biodiversity. Here we report on the state-of-the-art for each of these topics and in a final chapter we indicate the next steps that will be taken in the project.